2022
DOI: 10.1111/jcmm.17203
|View full text |Cite
|
Sign up to set email alerts
|

MST1/2 inhibitor XMU‐MP‐1 alleviates the injury induced by ionizing radiation in haematopoietic and intestinal system

Abstract: The Hippo signalling pathway has been considered as potential therapeutic target in self‐renewal and differentiation of stem and progenitor cells. Thus, mammalian Ste20‐like kinase 1/2 (MST1/2) as the core serine‐threonine kinases in the Hippo signalling pathway has been investigated for its role in immunological disease. However, little information of MST1/2 function in bone marrow suppression induced by ionizing radiation was fully investigated. Here, we reported that MST1/2 inhibitor XMU‐MP‐1 could rescue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The exposure to high doses of ionizing radiation can induce significant body weight loss and lead to animal death. For instance, the body weight of mice exposed to whole-body gamma irradiation in a dose of 8 Gy decreased by 15% on day 14 [ 31 ], in a dose of 7.5 Gy—on day 9 [ 45 ]. It was shown that the mouse survival rate on day 30 was 20% [ 31 , 46 ] or 13% [ 47 ] after whole-body gamma irradiation in a dose of 8 Gy and 33% after X-ray irradiation in a dose of 7 Gy [ 24 ], while the first deaths of animals were recorded on days 9, 5, 10, or 6, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to high doses of ionizing radiation can induce significant body weight loss and lead to animal death. For instance, the body weight of mice exposed to whole-body gamma irradiation in a dose of 8 Gy decreased by 15% on day 14 [ 31 ], in a dose of 7.5 Gy—on day 9 [ 45 ]. It was shown that the mouse survival rate on day 30 was 20% [ 31 , 46 ] or 13% [ 47 ] after whole-body gamma irradiation in a dose of 8 Gy and 33% after X-ray irradiation in a dose of 7 Gy [ 24 ], while the first deaths of animals were recorded on days 9, 5, 10, or 6, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, XMU-MP-1, a potent MST1/2 inhibitor, is sufficient to rescue irradiation-induced bone marrow damage ( 38 ). In mice, a significant decrease in blood cell counts and reduction of immune cell portion in the BM are observed from 4 Gy of total body irradiation.…”
Section: Hematopoietic Stem Cellmentioning
confidence: 99%
“…Similarly, in Xenopus primitive hematopoiesis model, Mst1/2 play significant roles in cell differentiation from hematopoietic and endothelial progenitors (37). http://bmbreports.org On the other hand, XMU-MP-1, a potent MST1/2 inhibitor, is sufficient to rescue irradiation-induced bone marrow damage (38). In mice, a significant decrease in blood cell counts and reduction of immune cell portion in the BM are observed from 4 Gy of total body irradiation.…”
Section: Hematopoietic Stem Cellmentioning
confidence: 99%
“…It is concerning that the rapid development of nuclear technology and its expanding application in the fields of medicine, industry, and military have only extended the casualty of mishaps due to irradiation to thousands of personnel [ 2 , 3 ]. The hematopoietic system in the human body is the most vulnerable to irradiation, and a hematopoietic injury could surface even at irradiation of less than 1 Gy, with the symptoms of diminished blood cell count conditions, such as anemia, thrombocytopenia, and particularly leukopenia [ 4 , 5 ]. The increasing scenarios of tension among the armed forces of different nations and terrorist threats, combined with the widespread application of radiation in oncology, have rendered it almost impossible to prevent radiation exposure, which underscores the prevalence of hematopoietic injury and the associated death rates.…”
Section: Introductionmentioning
confidence: 99%